PRESS COVERAGE OF THE PROCESSES OF TRANSITION TO MARKET ECONOMY RELATIONS (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article covers the analysis of the specific features of the coverage of processes of the transition to market relations of our Republic in media, especially in press. This problem is revealed on the basis of the analysis of articles published in the press, especially regarding the “Uzbek model” of development.